A better understanding of daily life abdominal wall mechanical solicitation: Investigation of intra-abdominal pressure variations by intragastric wireless sensor in humans. (June 2022) - Soucasse, Andréa; Jourdan, Arthur; Edin, Lauriane; Gillion, Jean-François; Masson, Catherine; Bege, Thierry
Highlights: Complete characterization of intra-abdominal pressure daily life variations. Assessment of intra-abdominal pressure by a wireless method with limited risk and discomfort. Evaluation including pressure variations, pressures rates and occurrence of pressure peaks. First-time recording of intra-abdominal pressure in healthy subjects during daily-life. Abstract: Intra-abdominal pressure (IAP), as the main mechanical load applied to the abdominal wall, is decisive in the occurrence of ventral hernia. The objective of the study was to propose a comprehensive evaluation of IAP based on a limited risk and discomfort method. A prospective study was carried out in 20 healthy volunteers. The intragastric pressure, validated for estimating IAP, was assessed by an ingestible pressure sensor. Volunteers realized a set of supervised exercises, then resumed their daily activities with the pressure continuously recorded until gastric emptying. Coughing and jumping exercises resulted in the highest IAP levels with maximum peaks of 65 ± 35 and 67 ± 31 mmHg and pressure rates of 121 and 114 mmHg. s −1 respectively. The position did not affect the IAP variation. Men had significantly higher pressure values for pushing against a wall ( P < 0.01 ), Valsalva maneuver and legs raising ( P<0.05 ) exercises. During daily life, IAP greater than 50, 100, and 150 mmHg occurred on average five times, twice, and once per hour, respectively. This study provides a real-life characterization of the IAP allowing the quantification of mechanical solicitation applied to the abdominal wall and the identification of risk situations for the occurrence of ventral hernias.